Development of a fuel cell and energy storage system for microgrid - Loh, Yuting (2014)
Microgrid is a new concept in power generation. They are modern and small-scale type of electrical systems whose primary goal is to diversify energy sources, and reduce carbon emission.Therefore, different type of distributed energy sources (DERs) systems